“obtención de harina de la hoja de ramio (boehmeria nivea), para uso como alimento animal” - Pérez Del Aguila, David (2006)
The present work was developed in the Laboratory of Engineering and Projects and the Laboratory of Food analysis of the Agro-industrial Engineering School, and is oriented to find parameters for the dehydration of ramio leaves (Boehmeria nivea), species of high nutritious value and that adapts satisfactorily to the environmental conditions of San Martín region. Determinations of proximal analysis were made, obtaining values of 87.03% for humidity, 2.82% for proteins, 0.7% for lipids, 2.4% for ashes, 1.62% for fiber and 5.43% for free nitrogen extract, in the fresh material, whereas in the dehydrated product were obtained values of 8.68% for humidity, 19.79% for proteins, 4.92% for lipids, 16.85% for ashes, 11.37% for fiber and 38.39% for free nitrogen extract. For the drying it was used a convective drying equipment of laboratory with velocity and temperature variables of drying air; throughout this process controlled the weight loss in the leaves, at intervals of time defined for the different conditions of temperature (40°C, 500C and 60ºC) and air velocity (0.5 mis, 0.8 mis and 1.1 mis) used. The water diffusivity in the ramio leaves was calculated fitting the Fick's model for infinite slab, using the program Microcal Origin 3.5, determining a good degree of adjustment with the experimental drying dates and values for this property that go from 0.804x10·10 m2/s to 3.23x10·10 m2/s, when the temperatura is increased of 400C to 600C. The calculated drying velocity was of 1.5, 2 and 3 kglh rrí2 for the temperatures of 40°C, 50ºC and 60ºC, respectively. The luminosity of the dry leaves variad between 33 and 37 units of color. The obtained flour crossed in a 60% the mesh of 180 microns, and the apparent digestibility was of34.78, which makes recommendable for animal feeding.